ANALISIS PENILAIAN TINGKAT KESEHATAN BPR DENGAN METODE CAMEL: STUDI KASUS BANK PASAR PATMA KLATEN - Alvian Rommy Kurniawan (Jurnal Ilmu Administrasi dan Bisnis, 2019)
CAMEL or capital aspect ratio (Capital Adequacy Ratio), productive asset quality aspect using KAP (Earning Asset Quality) and PPAP (Allowance for Elimination of Earning Assets), management aspect using general management and risk management calculation, aspect of rentability using ROA (Return On Assets) and BOPO (Operating Expenses to Operating Income), and liquidity aspects using the ratio of Cash Ratio and LDR (Loan to Deposit Ratio). CAMEL method used in data analysis based on Decree of Director of Bank Indonesia Number 30/12 / KEP / DIR dated April 30, 1997 concerning BPR Health Level Assessment Procedure. To determine the level of health of a bank after assessing each variable, by determining the results of the research classified as BPR's health predicate. Data obtained from financial statement in the form of balance sheet and income statement KBPR Bank Pasar Patma 2012-2016. Based on the results of the research conducted at KBPR Bank Patma Market stated that the level of health of KBPR Pasar Patma Bank period from 2012 to 2016 got healthy predicate because CAMEL credit value more than 81 (healthy minimum limit) that is 98,4 in 2012, 98,2 in 2013, 93.4 in 2014, 93.4 in 2015 and 93.2 in 2016. Keywords: CAMEL method, healthy rural level, BPR Pasar Patma Klaten.